Comparison of otoacoustic emissions in tinnitus and hyperacusis in adults with normal hearing sensitivity. (2nd May 2023) - Tai, Yihsin; Mertes, Ian B.; Chappell, Jenise; Jeon, Carolyn H.; Husain, Fatima T.
Abstract: Objective: To investigate the effect of tinnitus and/or hyperacusis on distortion product otoacoustic emission (DPOAE) measures in adults with normal hearing thresholds from 0.25 to 8 kHz, while accounting for extended high-frequency (EHF) thresholds. Design: A behavioural study consisted of comprehensive audiological assessment, validated tinnitus and hyperacusis questionnaires, DPOAE amplitudes and input/output (I/O) functions. Study sample: Data of 56 participants with normal hearing were included for the analysis. Participants were categorised into four groups: (1) without tinnitus or hyperacusis, (2) with tinnitus only, (3) with hyperacusis only, and (4) with both tinnitus and hyperacusis. Results: The groups with tinnitus showed elevated EHF thresholds compared with those without tinnitus. DPOAE amplitudes were not significantly affected by tinnitus and/or hyperacusis status; however, they were significantly affected by EHF thresholds. Further, no appreciable differences in DPOAE I/O functions were found across groups. Conclusions: The reported non-significant differences in DPOAEs in individuals with tinnitus and/or hyperacusis do not support a peripheral mechanism or an interaction between peripheral and central mechanisms underlying tinnitus or hyperacusis. Our findings, however, suggest the need to assess basal cochlear function (e.g. EHF thresholds) for a better understanding of differences in DPOAE measures in tinnitus and/or hyperacusis.